Gambaran Radiologis pada Bidang Neurologis Tumor Otak - Mauly Ilawanda, Zanetha; Faesal Atsani, Genta (CV RIFAINSTITUT, 2021)
Along with increasing life expectancy and advances in medical technology, the incidence of brain tumors continues to increase. Brain tumors can cause changes in mental status, neurological deficits, and create a large social burden. The incidence of benign brain tumors is 71% and these benign brain tumors develop twice as often in women as in men. Diagnosis brain tumors requires radiological examinations that can quickly diagnose brain tumors and must be done immediately. Source searches were carried out on the online portal of journal publications as many as 20 sources from MedScape, Google Scholar and the Nation Center for Biotechnology Information / NCBI with the keywords